2011
DOI: 10.2340/00015555-1111
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Use of Topical Medications and Socio-economic Data in Hand Eczema: A Swedish Nationwide Survey

Abstract: Hand eczema is common and has an adverse impact on the lives of patients. There is a need for population-based surveys on the pharmacoepidemiological aspects, quality of life and impact of socioeconomic factors in hand eczema. The aim of this cross-sectional study was to investigate these factors. A questionnaire-based nationwide survey of health was performed, including questions on hand eczema, use of pharmaceuticals and socioeconomic factors. Quality of life was estimated with the generic instrument Short F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
3
11
1
Order By: Relevance
“…One of the most striking cases is that of skin conditions, which in our study were relatively strongly concentrated in more deprived communities, while other authors have found no relationship between poor socioeconomic conditions and this type of health problem [27,29]. Nevertheless, such an association has been established for certain dermatological conditions [30], so that it seems reasonable to suppose that an analysis separating dermatologic problems into smaller and less heterogeneous groups might have found various types of relationship between social factors and these conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…One of the most striking cases is that of skin conditions, which in our study were relatively strongly concentrated in more deprived communities, while other authors have found no relationship between poor socioeconomic conditions and this type of health problem [27,29]. Nevertheless, such an association has been established for certain dermatological conditions [30], so that it seems reasonable to suppose that an analysis separating dermatologic problems into smaller and less heterogeneous groups might have found various types of relationship between social factors and these conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…From a socio-economic point of view, 55% of the women with hirsutism were gainfully employed, which is a lower proportion compared to the figure reported for the general female population in Sweden [ 45 ]. As for HRQoL, the results of this study demonstrate that all dimensions in the SF-36 were significantly lower compared to a Swedish normal population sample, but in accordance with patients with severe dermatological states, such as severe psoriasis [ 46 ], severe hand eczema [ 28 ] and ichtyosis [ 47 ]. The dimensions with the most impaired health were Vitality, Social Functioning, Role Emotional and Mental Health.…”
Section: Discussionsupporting
confidence: 54%
“…A Swedish normal sample was recruited from a nationwide survey based on a questionnaire on subjectively perceived health, quality of life (SF-36), and use of medication [ 28 ]. Sweden keeps a population register based on the unique personal number held by all people who are legal residents in the country.…”
Section: Methodsmentioning
confidence: 99%
“…Hand eczema is 1.5 – 2 times more common in females compared with males [2,3]. Swedish estimates of 1-year prevalence of hand eczema in different age-groups have varied from 6.5% to 11.8% [4-6]. Among Swedish 20–29 year-olds, the 1-year prevalence of hand eczema was reported to range from 7.5% to 10.8% [3,4].…”
Section: Introductionmentioning
confidence: 99%